2018
DOI: 10.1002/anie.201803859
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanosheets by Morphology‐Retained Carbonization of Two‐Dimensional Assembled Anisotropic Carbon Nanorings

Abstract: Two-dimensional (2D) carbon nanomaterials possessing promising physical and chemical properties find applications in high-performance energy storage devices and catalysts. However, large-scale fabrication of 2D carbon nanostructures is based on a few specific carbon templates or precursors and poses a formidable challenge. Now a new bottom-up method for carbon nanosheet fabrication using a newly designed anisotropic carbon nanoring molecule, CPPhen, is presented. CPPhen was self-assembled at a dynamic air-wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 34 publications
0
48
0
2
Order By: Relevance
“…The thickness of the nanosheet was determined to be approximately 3.5 nm according to atomicf orce microscopy (AFM)a nalysis( Figure1f), which is rather thinner than most previously reported 2D materials in the literature (10 nm for NCNS;4 8nmf or meso/micro-FeCo-N x -CN;2 0-35 nm for 2D poly(polyethyleneg lycol citrate-co-N-isopropylacrylamide) (PPCN)). [39][40][41] The number of graphite layers for 2D Fe-N-CNSw as determined to be approximately ten given that the interlayer spacing of graphite layers was calculated to be 0.377 nm according to the Bragg equation, as indicated by XRD patterns.T he influence of the KCl/FeTCPPCl mass ratio or heat-treatment temperature on the morphology was also exploredb ymeans of SEM (Figures S5 and S6 in the Supporting Information). It was observed that the morphology of the KCl/ FeTCPPCl sheets was almostu nchanged, but the thickness of the 2D Fe-N-CNS decreaseda st he KCl/FeTCPPCl ratio increased.…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of the nanosheet was determined to be approximately 3.5 nm according to atomicf orce microscopy (AFM)a nalysis( Figure1f), which is rather thinner than most previously reported 2D materials in the literature (10 nm for NCNS;4 8nmf or meso/micro-FeCo-N x -CN;2 0-35 nm for 2D poly(polyethyleneg lycol citrate-co-N-isopropylacrylamide) (PPCN)). [39][40][41] The number of graphite layers for 2D Fe-N-CNSw as determined to be approximately ten given that the interlayer spacing of graphite layers was calculated to be 0.377 nm according to the Bragg equation, as indicated by XRD patterns.T he influence of the KCl/FeTCPPCl mass ratio or heat-treatment temperature on the morphology was also exploredb ymeans of SEM (Figures S5 and S6 in the Supporting Information). It was observed that the morphology of the KCl/ FeTCPPCl sheets was almostu nchanged, but the thickness of the 2D Fe-N-CNS decreaseda st he KCl/FeTCPPCl ratio increased.…”
Section: Resultsmentioning
confidence: 99%
“…[86] Ther esulting arrays of fullerene nanowhiskers can operate as as caffold for the highly aligned growth of living cells,r esulting in hierarchical molecule-nanomaterial-cell assemblies.T he vortex LB method was also used for preparation of two-dimensional nanocarbon films through self-assembly of carbon nanoring molecule,9 ,9',10,10'-tetra-butoxy-cyclo[6]-paraphenylene[2]-3,6-phenanthrenylene,u nder dynamic surface flow (Figure 15 B). [87] By selecting an appropriate rotation speed, as elf-assembled uniform few-nanometers-thick film of the carbon nanoring molecules was obtained. Thef ilm could be transferred onto asolid surface and was subjected to thermal carbonization.…”
Section: Langmuir-blodgett Methodsmentioning
confidence: 99%
“…Darüber hinaus wurde die Vortex-LB-Methode fürdie Darstellung zweidimensionaler Nanokohlenstofffolien mittels Selbstassemblierung von Kohlenstoffnanoringen, 9,9',10,10'-Tetrabutoxycyclo[6]paraphenylen[2]-3,6-phenanthrenylen, unter einem dynamischen Oberflächenfluss benutzt (Abbildung 15 B). [87] Durch die Wahl einer geeigneten Rotationsgeschwindigkeit wurde eine selbstassemblierte gleichmäßige wenige Nanometer dicke Folie aus Kohlenstoffnanoringmolekülen erhalten. Die Folie konnte auf eine feste Oberfläche übertragen werden und wurde einer thermischen Karbonisierung unterworfen.…”
Section: Langmuir-blodgett-technologieunclassified